Maximizing Learning During Covid-19: Boosting Teachers' Competence with Office 365 - Bambang Cahyono; Dydik Kurniawan; Tri Wahyuningsih (Universitas Muhammadiyah Sidoarjo, 2023)
The aim of this study was to improve teachers' competence and the implementation of Office 365 in learning during the COVID-19 pandemic. The method used in this study was Planning, Implementation, and Evaluation. The participants of the study were 90 teachers from all levels of education in Indonesia, who were trained by three lecturers from FKIP Mulawarman University and one teacher from SMP IT Madina. The results showed an increase in the participants' competence in using Office 365 to support learning in schools during the pandemic. Office 365 was found to be a viable alternative to support the teaching and learning process in schools. The implication of this study is that Office 365 can be used as a tool to facilitate the learning process during the pandemic, and training programs can be developed to improve teachers' competence in using this technology. Highlights Office 365 can be used as an alternative tool for supporting the learning process during the pandemic. The training program improved teachers' competence in utilizing Office 365 for learning purposes. The study involved 90 teachers from all levels of education in Indonesia. The training program was carried out through Planning, Implementation, and Evaluation methods.